2000
DOI: 10.1126/science.289.5481.947
|View full text |Cite|
|
Sign up to set email alerts
|

A Single Adenosine with a Neutral p K a in the Ribosomal Peptidyl Transferase Center

Abstract: Biochemical and crystallographic evidence suggests that 23S ribosomal RNA (rRNA) is the catalyst of peptide bond formation. To explore the mechanism of this reaction, we screened for nucleotides in Escherichia coli 23S rRNA that may have a perturbed pKa (where Ka is the acid constant) based on the pH dependence of dimethylsulfate modification. A single universally conserved A (number 2451) within the central loop of domain V has a near neutral pKa of 7.6 +/- 0.2, which is about the same as that reported for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
165
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(181 citation statements)
references
References 30 publications
6
165
1
4
Order By: Relevance
“…The proximity of the N3 of A2486 (2451 in Escherichia coli) to the attacking ␣ amino group and the analogue of the tetrahedral intermediate led to the suggestion that A2486 (2451) may function as a general acid͞base during peptide bond formation. This hypothesis appeared to be supported by data on the pH dependence of its chemical reactivity and the finding that mutations of A2486 are dominant lethal in vivo (12). Further, the interaction between the N3 of A2486 (2451) and the phosphate oxygen of the reaction intermediate observed in the structure implied an altered pKa (8).…”
supporting
confidence: 60%
“…The proximity of the N3 of A2486 (2451 in Escherichia coli) to the attacking ␣ amino group and the analogue of the tetrahedral intermediate led to the suggestion that A2486 (2451) may function as a general acid͞base during peptide bond formation. This hypothesis appeared to be supported by data on the pH dependence of its chemical reactivity and the finding that mutations of A2486 are dominant lethal in vivo (12). Further, the interaction between the N3 of A2486 (2451) and the phosphate oxygen of the reaction intermediate observed in the structure implied an altered pKa (8).…”
supporting
confidence: 60%
“…We found that twister does not have a HB donor with good geometry and a chemical group with a reasonable pK A to act as a general acid. The only HB donor with reasonable geometry is the N3 of A10, but this nitrogen has a very low pK A of about -4.2 to 1.0 (22,23). Although this would be a great chemical group to interact with the 5′-OH leaving group, it would require a highly perturbed pK A to act as a general acid.…”
Section: Discussionmentioning
confidence: 99%
“…Among the myriad of molecules that existed in the RNA-world, a population of them was involved in the origin of translation, whereby it has been sensibly suggested that the original function of the ribosome was RNA replication via triplets, not translation . We can take it as a given that at some point a precursor of the peptidyl transferase reaction (Muth et al 2000) of an RNA molecule did evolve, and the chance stereochemistry of that molecule would determine the decision of whether it could catalyse the polymerization of d-or lamino acids into peptides. That filter would be sufficient to tip the holochirality scale, because despite the presence of a racemate, only amino acids of the same a-carbon configuration would preferentially end up in peptides, yielding a population of distinctly handed peptides, some of which would eventually need to feed back in a hypercycle-like manner (Eigen & Schuster 1978) into favoured synthesis of their stereochemically correct polymerizing template.…”
Section: Holochiralitymentioning
confidence: 99%